Urban Tourism as a Source of Contention and Social Mobilisations: A Critical Review. Issue 4 (4th July 2019) - Novy, Johannes; Colomb, Claire
ABSTRACT: Across the globe, there has been a proliferation of manifestations of discontent and protest around tourism-related issues in cities. This points to an increasing "politicisation from below" of the impacts of the visitor economy on people and places, which is the result of the quantitative and qualitative transformation of urban tourism, and of the ways in which tourism has been governed (or not) in contemporary cities. This critical review discusses the variety of tourism-related social mobilisations recently witnessed in cities. It distinguishes between multi-focal versus single-issue mobilisations; between those purposefully and primarily focused on tourism and those which have integrated tourism within broader urban struggles; between those with a radical, progressive agenda for urban change versus those primarily defending narrower interests or exhibiting reactionary or hostile characteristics. The paper ends by discussing how urban governance and public policies have responded so far to the conflicts and social mobilisations around tourism.